Reliability of handgrip strength test in basketball players - Gerodimos, V. (Journal of Human Kinetics, 2012)
Handgrip strength is important in basketball as various movements rely on the continuous use of wrist and digits flexor muscles when catching, holding, shooting and throwing the ball. Therefore, the assessment of handgrip strength is used in prepubertal, adolescent and adult basketball players. The reliability of handgrip strength may be influenced by several factors including age. The purpose of this study was to examine the reliability of handgrip strength in basketball players from childhood to adulthood. Male basketball players (n = 90) were assigned into three groups: prepubertal (9.8 +/- 0.7yrs), adolescents (14.4 +/- 0.6yrs), and adults (26.1 +/- 5.6yrs). Each participant performed three maximal isometric contractions on each hand in two occasions, one day apart. Intraclass correlation coefficient (ICC), standard error of measurement (SEM) and 95% limits of agreement (LOA) were calculated. The test-retest reliability was high for both preferred (ICC = 0.94 +/- 0.98) and non-preferred (ICC = 0.96 +/- 0.98) hands, without differences in reliability among age-groups. The results showed a significant age-related increase (p < 0.05) in absolute and relative handgrip strength irrespective of hand preference. The present results indicate that maximum handgrip strength can be measured reliably, using the Jamar hand dynamometer, in basketball players from childhood to adulthood.